2003
DOI: 10.1023/b:ccfp.0000006294.88201.68
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Child Exposure to War and Terrorism

Abstract: Acts of war and terrorism are increasingly prevalent in contemporary society. Throughout history, weaponry has become more efficient, accurate, and powerful, resulting in more devastation and loss of human life. Children are often overlooked as victims of such violence. Around the world, children are exposed to violence in multiple forms, frequently developing traumatic stress reactions. Such reactions are best understood within the context of social-emotional and cognitive development, as children respond dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(98 citation statements)
references
References 62 publications
5
88
0
5
Order By: Relevance
“…Sevilen kişilerin kaybı, yer değiştirme, sıkıntı içersindeki erişkinlerle yaşa-ma, geleneksel yaşam biçiminin kaybı, eğitim altyapısının zarar görmesi, fiziksel çevrenin kötülüğü, toplumsal değişiklikler ve hatta çocukların şiddete yönlendirilmesi gibi çevresel etkenler yanısıra fiziksel kapasitenin kaybı, beden yapısının bozulması, patlama ile karşılaşma ve beslenme yetersizliği gibi doğrudan etkileyen unsurlar çocukların kırılgan olduğu konulardır (10) . Öte yandan, terör ve savaş travmalarının etkilerinin kuşaktan kuşağa devredilebildiği de bilinmektedir (11) .…”
Section: Ruhsal Travma Ile İlgili Psikiyatrik Tablolarunclassified
“…Sevilen kişilerin kaybı, yer değiştirme, sıkıntı içersindeki erişkinlerle yaşa-ma, geleneksel yaşam biçiminin kaybı, eğitim altyapısının zarar görmesi, fiziksel çevrenin kötülüğü, toplumsal değişiklikler ve hatta çocukların şiddete yönlendirilmesi gibi çevresel etkenler yanısıra fiziksel kapasitenin kaybı, beden yapısının bozulması, patlama ile karşılaşma ve beslenme yetersizliği gibi doğrudan etkileyen unsurlar çocukların kırılgan olduğu konulardır (10) . Öte yandan, terör ve savaş travmalarının etkilerinin kuşaktan kuşağa devredilebildiği de bilinmektedir (11) .…”
Section: Ruhsal Travma Ile İlgili Psikiyatrik Tablolarunclassified
“…The violence of terrorism often results in a multitiered cascade of negative life events, including loss of loved ones, displacement, lack of educational structure, and drastic changes in daily routine and commu-nity values. These numerous losses, challenges, and stresses affect children's brains, minds, and bodies in an orchestrated whole-organism response (Joshi & O'Donnell, 2003). For instance, children and adolescents have had very different reactions to the 9/11 terrorist attacks on the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Research found that children and adolescents in the families affected by the organized violence are particular vulnerable group and may not only be affected by direct exposure to organized violence but also by indirect negative effects, such as family economic decline, lack of education and lasting familial conflict (Joshi & O'Donnell, 2003). This may be caused by the families experiencing poverty possess neither the material nor the psychological resources to protect their children from the pressures that accompany economic deprivation (Evans, 2004).…”
Section: Distal Context Poverty and Income Inequalitymentioning
confidence: 99%